2021
DOI: 10.1177/10711007211019940
|View full text |Cite
|
Sign up to set email alerts
|

Association of Visual Appearance on Outcomes After Hallux Valgus Surgery

Abstract: Background: In this study, our aim was to determine the effect of cosmetic improvement on patient satisfaction and functional scores in hallux valgus (HV) surgery. Methods: Preoperative foot photographs of 105 patients who had undergone chevron osteotomy for HV between 2016 and 2018 were taken. The patients were divided into 2 groups. Twenty-four months after surgery, the preoperative foot photographs were shown to patients in group 1 (n = 52) but not to patients in group 2 (n = 53). The groups were then compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The panel validated all the items relating to aesthetics, confirming reports in the literature that many individuals seek repair to improve the aesthetic appearance of their foot [ 43 , 45 , 69 ]. Furthermore, aesthetic perceptions may influence pain levels and the functional benefits of surgery [ 69 ]. Since hallux valgus repair should not be performed for cosmetic reasons [ 59 ], such motives must be ascertained preoperatively.…”
Section: Discussionsupporting
confidence: 68%
“…The panel validated all the items relating to aesthetics, confirming reports in the literature that many individuals seek repair to improve the aesthetic appearance of their foot [ 43 , 45 , 69 ]. Furthermore, aesthetic perceptions may influence pain levels and the functional benefits of surgery [ 69 ]. Since hallux valgus repair should not be performed for cosmetic reasons [ 59 ], such motives must be ascertained preoperatively.…”
Section: Discussionsupporting
confidence: 68%
“…when performing joint replacement surgery on patients with KOA and decide whether to intervene. Patients with HV have varying degrees of foot deformities, which can also cause pain and poor foot appearance [ 7 ]. Our findings serve as a reminder to clinicians to identify and intervene at an earlier stage in patients with osteoarthritis and hallux valgus.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review estimated that worldwide, the prevalence of HV is as high as 23% in people aged 18-65 years and 35% in people over 65 years [ 6 ]. The HV deformity can lead to functional disabilities, such as foot pain, compromised gait, diminished balance, and foot deformity,which can significantly impact a person's ability to walk comfortably and perform daily activities [ 7 10 ]. A study [ 11 ] revealed a noteworthy disparity in the occurrence of HV and knee osteoarthritis (KOA) among female patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study from Istanbul (Turkey) aimed to address the question of whether cosmetic appearance following surgery had any relationship with patient-reported functional outcome. 1 The authors reviewed the case However, the conclusions are somewhat undermined by the design. A study of this nature may be better performed with a prospective design and the two groups randomly assigned.…”
Section: Seeing Is Believing? Cosmetic Appearance and Patient-reporte...mentioning
confidence: 99%